Sacred and Profane in Music Therapy - Joscelyn Godwin (Religions, 2023)
The widespread belief that music has some therapeutic potential rests partly on demonstrable, practical results. But explaining how such therapy works depends on the belief system of the explainer or practitioner. This survey of the literature shows how strongly a discipline is affected by its underlying metaphysical presuppositions. Traditional explanations, from antiquity through the nineteenth century, include participation by God or the gods; music as a bearer of sacred and harmonic numbers; the doctrine of correspondences and occult sympathies; the presence of animal spirits, subtle fluids, and other non-material elements in the human compound. The official belief system of the modern medical establishment cannot allow for any of these, hence its attempt to find materialistic explanations of how music therapy works. In the late 20th century some therapists, rejecting this constraint, returned to a more spiritual approach.